2021
DOI: 10.3390/foundations1010007
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Existence Results for Boundary Value Problems of Hilfer Fractional Differential Equations and Inclusions

Abstract: This paper is a survey of the recent results of the author for various classes of boundary value problems for Hilfer fractional differential equations and inclusions of fractional order in (1,2] supplemented with different kinds of nonlocal boundary conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Substituting the constants c 1 and c 2 into (18), we obtain the integral equation in (15) as desired.…”
Section: Lemma 1 ([2]mentioning
confidence: 99%
See 1 more Smart Citation
“…Substituting the constants c 1 and c 2 into (18), we obtain the integral equation in (15) as desired.…”
Section: Lemma 1 ([2]mentioning
confidence: 99%
“…Numerous monographs have appeared devoted to fractional differential equations, for example, see [1][2][3][4][5][6][7][8]. Recently, differential equations and inclusions equipped with various boundary conditions have been widely investigated by many researchers (see [9][10][11][12][13][14][15][16][17][18] and the references cited therein).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many papers in the literature have been devoted to the study of fractional differential equations and inclusions defined by the Hilfer fractional derivative (e.g., [8][9][10][11] etc.). We point out that a complete survey on this field of study may be found in [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many papers in the literature have been devoted to the study of fractional differential equations and inclusions defined by the Hilfer fractional derivative (e.g., [8][9][10][11] etc.). We point out that a complete survey on this field of study may be found in [8]. Taking into account this new trend in research, our intention is to contribute to the development of this topic by establishing new results for a particular class of problems.…”
Section: Introductionmentioning
confidence: 99%
“…The greater part of the current work is concentrated on the existence and uniqueness of the solution for FEE (see [14][15][16]). The goal of this study is to investigate the existence of solutions to a class of multiterm FFEE on an unbounded interval in terms of bounded and consistent capacities.…”
Section: Introductionmentioning
confidence: 99%